Philosophy: The World's Greatest Thinkers - Stokes, Philip (London Arcturus Publishing Limited, 2011)
Concise and informative, this book provides an ideal introduction to philosophical ideas and the effect they have had on the wider world. Both easy to use and a stimulating read, this is an ideal reference for anybody interested in philosophy and provides a clear, entertaining exposition of the ideas that have shaped the way we think.
Keywords: The World's Greatest Thinkers